KR-12-a6 promotes the osteogenic differentiation of human bone marrow mesenchymal stem cells via BMP/SMAD signaling - Fu, Lanqing (Mol Med Rep, 2020)
Considering the increased resistance to antibiotics in the clinic and the ideal antibacterial properties of KR-12, the effects of KR-12-a6, an important analogue of KR-12, on the osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs) were investigated. Osteogenic differentiation-associated experiments were conducted in hBMSCs, and KR-12-a6 was used as an additional stimulating factor during osteogenic induction. Quantitative analysis of alkaline phosphatase (ALP) and alizarin red staining, and reverse transcription-quantitative PCR analysis of the expression of osteogenesis-associated genes were performed to determine the effects of KR-12-a6 on the osteogenic differentiation of hBMSCs. LDN-212854 was selected to selectively suppress BMP/SMAD signaling. Western blotting was performed to investigate the underlying mechanisms. The intensity of ALP and alizarin red staining gradually increased with increasing KR-12-a6 concentrations. KR-12-a6 induced the strongest staining at 40 µg/ml, whereas 60 µg/ml and 80 µg/ml concentrations did not further increase the intensity of staining. The mRNA expression levels of RUNX2 and ALP increased in a dose-dependent manner as early as 3 days post-KR-12-a6 treatment. The mRNA expression of COL1A1, BSP and BMP2 exhibited significant upregulation from day 7 post-KR-12-a6 treatment. In contrast, the mRNA levels of OSX, OCN and OPN were enhanced dramatically at day 14 following KR-12-a6 stimulation. Additionally, KR-12-a6 significantly promoted the phosphorylation of Smad1/5. Furthermore, LDN-212854 suppressed the activation of Smad1/5 and inhibited the upregulation of several osteogenic differentiation-associated genes in KR-12-a6-treated hBMSCs. KR-12-a6 promoted the osteogenic differentiation of hBMSCs via BMP/SMAD signaling.